2010
DOI: 10.1111/j.1365-2133.2010.09940.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1, angiopoietin-2 and Tie-2 receptor expression in human dermal wound repair and scarring

Abstract: These data demonstrate that angiopoietins and their receptor, Tie-2, are expressed in both fibroblasts/myofibroblasts and endothelial cells in healing human wounds. Fibroblast/myofibroblast expression correlates with angiogenesis and VEGF expression, suggesting a role for the angiopoietin/Tie-2 system in normal wound repair and scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
3
39
0
1
Order By: Relevance
“…For example, after tissue injury, healing occurs through an initial phase of angiogenesis followed by tissue fibrosis or regeneration. In both instances, the early phase is associated with enhanced expression of Angpt2 and Vegfa expression locally around the wound; Vegfa is upregulated in keratinocytes, whereas Angpt2 is increased in endothelial cells (13,26). Accordingly, we induced a controlled tissue injury using an ear punch (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, after tissue injury, healing occurs through an initial phase of angiogenesis followed by tissue fibrosis or regeneration. In both instances, the early phase is associated with enhanced expression of Angpt2 and Vegfa expression locally around the wound; Vegfa is upregulated in keratinocytes, whereas Angpt2 is increased in endothelial cells (13,26). Accordingly, we induced a controlled tissue injury using an ear punch (27).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that ANGPT1 showed the statistically significant decrease in mRNA expression 1 day after the skin incisions. These factors have been reported to promote angiogenesis [6,[19][20][21]23,27,33,34], and their decreases may indicate that complex mechanisms may be involved in our skin wound system.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined mRNA expressions of factors possibly involved in angiogenesis in the rat skin incision wounds, using TaqMan probes. The factors studied are: angiopoietin (ANGPT) 1 and 2 [6][7][8], cadherin 5 (CDH5) [9], granulocyte-macrophage colony stimulating factor (CSF2/GM-CSF) [10][11][12][13], granulocyte colony stimulating factor http://dx.doi.org/10.1016/j.legalmed.2015.02.007 1344-6223/Ó 2015 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…60 Angiopoietin-2 is expressed from day 3 of dermal wound healing 61 and is present during reepithelialization, granulation tissue formation, and remodeling. 62,63 Binding of the angiopoietin-2 FBG domain to Tie2 receptor mediates the destabilization of existing vessels promoting vascular remodeling in the presence of vascular endothelial growth factor (VEGF). 64 In addition, it can promote endothelial cell survival.…”
Section: Patterns [Damps]mentioning
confidence: 99%